Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Moderasi Pada Perusahaan Subsektor Semen Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2021-2024 - Ravina Mayanda Putri; Mulatsih Mulatsih (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of profitability, firm size, and leverage on firm value with dividend policy as a moderating variable in cement sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research employed a purposive sampling technique and selected 7 companies with a total of 28 observations. The analytical methods used were multiple linear regression and Moderated Regression Analysis (MRA) with the assistance of SPSS version 26. The results indicate that profitability and firm size do not have a significant effect on firm value, while leverage has a significant effect on firm value. Furthermore, dividend policy is not able to moderate the relationship between profitability, firm size, and leverage on firm value. These findings imply that firm value in cement companies is more influenced by leverage rather than profitability or company size, and dividend policy fails to strengthen or weaken the relationship between the independent and dependent variables.